GIS-Based Rainfall Estimator Evaluation and Interpolation Analysis Using ArcGIS - Joe Yuan Mambu (Fakultas Ilmu Komputer, Universitas Klabat, 2018)
We have been always trying to predict the weather to minimize risk, produce strategy, and other decision making situation. To achieve this, monitoring method need to be used to gather data. Rainfall monitoring is one of the area that widely used and one of the mostly used method is satellite-based rainfall monitoring. However, there are limitation to apply to the Satellite Rainfall (SR) estimation specifically on its accuracy and lack of certainty. Thus, study that directed to measure the inaccuracies of SR measurements is needed by using data of distribution of Actual Rainfall (AR). The SR data is taken from the National Oceanic and Atmospheric Administration (NOAA)’s Hydro—Estimator while the AR data was from the National Institute of Water and Atmospheric Research (NIWA). Through the statistics and interpolation analysis using ArcGIS, the study shows a prominent result of SR estimation accuracy in the sample area and thus may opens up more similar implementation as well as stands as a good benchmark for future improvement of the method. This study also shows how interpolation method through a GIS software could provide a significant result on a geographical related studies. Keywords : GIS, Geospatial Analysis, Interpolation Analysis, Arcgis